Permanence in Multispecies Nonautonomous Lotka-Volterra Competitive Systems with Delays and Impulses - Xiaomei Feng; Fengqin Zhang; Kai Wang; Xiaoxia Li (Discrete Dynamics in Nature and Society)
This paper studies multispecies nonautonomous Lotka-Volterra competitive systems with delays and fixed-time impulsive effects. The sufficient conditions of integrable form on the permanence of species are established.